Performance assessment and design improvements for an urban coastal detention basin under intensifying rainfall extremes - Chathuranika, Imiya Mudiyanselage; Asante, Agyare; Borhani, Faeghe; Wang, Xixi; Erten-Unal, Mujde; Ismael, Dalya (Frontiers in Built Environment, 2026)
Coastal urban areas are increasingly exposed to flooding driven by more frequent and intense rainfall events, rising sea levels, and expanding impervious surfaces. Norfolk, Virginia, a low-lying coastal city with aging stormwater infrastructure, faces heightened vulnerability to these hydrologic pressures. This study evaluates the hydraulic performance of an existing urban detention basin within the Edgewater–Larchmont catchment under 10-, 50-, and 100-year, 2-h design storms using the U.S. Environmental Protection Agency’s Storm Water Management Model (SWMM). Simulations were conducted for both pre- and post-development conditions to assess changes in peak discharge, storage capacity, and water level dynamics. Results show that urbanization, which increased impervious area from 5% to 70%, substantially intensified runoff generation. Peak discharges increased from 1.44 m3/s under pre-development 10-year conditions to 2.81 m3/s and 3.51 m3/s under post-development 50-year and 100-year storms, respectively, while total runoff volumes approximately doubled. Although total basin storage capacity was not exceeded, the detention basin became hydraulically limited during extreme storms as effective storage below the outlet elevation was rapidly exhausted, leading to elevated peak outflows. Outlet elevation adjustments that increased effective detention storage improved flow attenuation and reduced post-development peak discharges toward pre-development levels. This highlights the value of integrating hydrologic modeling with adaptive infrastructure design to enhance flood resilience and support evidence-based, climate-adaptive stormwater planning.